Null subjects, preproprial articles, and the syntactic structure of Old Norwegian pronouns - Johnsen, Sverre Stausland (Norsk Lingvistisk Tidsskrift, 2017)
In Old Norwegian (ON), 1st and 2nd person null subjects (1/2 NS) are much rarer than 3rd person null subjects (3 NS). It has been suggested in recent work that 1/2 NS are ungrammatical and in fact do not exist in ON. According to this view, only 3rd person pronouns can be null subjects, because only they are not DPs (determiner phrases). For this latter claim to be true, ON cannot have preproprial articles, as this would indicate that 3rd person pronouns are DPs. This article presents ON data to demonstrate that the language has both 1/2 NS and preproprial articles. Since all ON personal pronouns appear to be DPs, there is little support for the purported difference in syntactic structure; thus, the observed asymmetry between 1/2 NS and 3 NS must have other, possibly extra-grammatical, causes.